RESIKO YURIDIS ASURANSI SOSIAL BAGI PEGAWAI PT TASPEN (PERSERO) KANTOR CABANG UTAMA SEMARANG YANG MENGAJUKAN PENSIUN DINI - Rahmat Hafidh; Fitika Andraini (Fakultas Hukum Universitas Stikubank, 2018)
PT TASPEN (PERSERO) is an Indonesian State-Owned Enterprise engaged in pension fund insurance and taboo PT TASPEN (PERSERO) is an Indonesian State-Owned Enterprise engaged in insurance for pension funds and old age savings which refers to Government Regulation Number 20 of 2013 About Amendments to Government Regulation Number 25 of 1981 concerning Civil Servants' Social Insurance. PT TASPEN (PERSERO) in carrying out its role is not always able to fulfill the rights of Civil Servants on pension rights and old age savings because of the things that are needed in the fulfillment of pension rights and old age savings. These matters are concerning the role of PT TASPEN (PERSERO) in organizing pension and old-age savings programs that will later be entitled to receive severance pay and receive other pension rights based on applicable regulations. The problem in this study is about the risk of social insurance juridical for employees of PT TASPEN (PERSERO) Semarang Main Branch Office who apply for early retirement before the specified retirement age limit. This research is a type of normative juridical research that focuses on studying the application of positive legal norms or norms. From the results of this study indicate that, the juridical risk when applying for an early retirement is not legal unless the person concerned is in trouble, at the time of retirement will get administrative sanctions in the form of postponement of retirement or severance pay. With old age referring to Government Regulation Number 20 of 2013 concerning Amendments to Government Regulation Number 25 of 1981 concerning Civil Servants' Social Insurance. PT TASPEN (PERSERO) in carrying out its role is not always able to fulfill the rights of Civil Servants on pension rights and old age savings because of the things that are needed in the fulfillment of pension rights and old age savings. These matters are concerning the role of PT TASPEN (PERSERO) in organizing pension and old-age savings programs that will later be entitled to receive severance pay and receive other pension rights based on applicable regulations.